Study of Verses of the Hisab Rukyah in Astronomical Perspective - Nursodik Nursodik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
The discourse of the verses of the Qur’an regarding the reckoning (hisab) and determining date by sighting of moon (rukyat) did not find passages that describe implicitly on an initial determination by using the lunar month of reckoning, but explicitly there are several verses in the Qur'an that mention reckoning in relation to the existence position of the moon and sun. The correlation or relationship verses of the Koran to the concept of astronomy (reckoning rukyah) based on the interpretations and asbab al-nuzul show harmony with the science of astronomy. Therefore, the science of astronomy is needed as a tool for understanding the verses of Allah in the Qur'an and in the universe. Thus signaling a clear and complete information about the procedure of reckoning and rukyat preliminary determination of the Moon in the Qur'an now we'll get to bridge the bridge between the message of the Qur'an and as-Sunnah (proposition syar'i), rukyat or observation and reckoning is required a comprehensive understanding of the objective - scientific paradigm in understanding the concept of reckoning and rukyah as a single entity that can not be separated.